2019
DOI: 10.1101/19001206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of malaria parasites in dried human blood spots using mid-infrared spectroscopy and logistic regression analysis

Abstract: Background: Epidemiological surveys of malaria currently rely on microscopy, polymerase chain reaction assays (PCR) or rapid diagnostic test kits for Plasmodium infections (RDTs). This study shows that mid-infrared (MIR) spectroscopy coupled with supervised machine learning could constitute an alternative method for rapid malaria screening, directly from dried human blood spots. Methods: Filter papers containing dried blood spots (DBS) were obtained from a cross-sectional malaria survey in twelve wards in sou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…To this end, two independent field trials have been undertaken in South Eastern Tanzania 124 and Thailand, 123 respectively. Mwanga et al 124 applied mid-IR spectroscopy coupled with supervised machine learning to screen malaria infection in dry blood spots obtained from 296 different volunteers. Samples were pre-analyzed with PCR and found to consist of 123 malaria positives and 173 malaria negatives.…”
Section: Application Of Ir Spectroscopy For Human Disease Diagnosis Parasitic Infectionsmentioning
confidence: 99%
“…To this end, two independent field trials have been undertaken in South Eastern Tanzania 124 and Thailand, 123 respectively. Mwanga et al 124 applied mid-IR spectroscopy coupled with supervised machine learning to screen malaria infection in dry blood spots obtained from 296 different volunteers. Samples were pre-analyzed with PCR and found to consist of 123 malaria positives and 173 malaria negatives.…”
Section: Application Of Ir Spectroscopy For Human Disease Diagnosis Parasitic Infectionsmentioning
confidence: 99%
“…Given the fact that more and more studies apply the deep learning algorithms for features extraction and construction [48], [49] and classification, a large amount of annotated image repositories is highly required for training to improve the classification accuracy. Mwanga et al proposed an approach that applies mid-infrared spectroscopy and logistic regression analysis to detect malaria parasites in dried human blood spots [16].…”
Section: B Applications Of Machine Learning Algorithmsmentioning
confidence: 99%
“…Image processing can be used to process the imageries captured using remote sensing devices [26]. In addition to that, image classification is also applied in classifying blood for humans infected by malaria disease [16].…”
Section: ) Data Capturing Phasementioning
confidence: 99%
“…Heraud et al [77] demonstrated that infrared (IR) analysis of packed RBCs using a portable spectrometer and a cloud-based SVM system could have the potential to become an accurate POC tool for the diagnosis of malaria in endemic countries. Furthermore, another study [78] also employed IR spectroscopy in combination with supervised ML to screen for malaria parasites in human dried blood spots. The authors found that Logistic Regression appeared to be the best performing model with overall accuracies of 92% for predicting Plasmodium falciparum infections and 85% in predicting mixed infections of Plasmodium falciparum and Plasmodium ovale.…”
Section: Malaria Diagnosismentioning
confidence: 99%
“…While MALDI-TOF MS is commonly used for microbial identification in the routine clinical microbiology lab, vibrational spectroscopy (i.e. IR and Raman spectroscopy) is gaining considerable interest as an alternative technique in the classification of clinically relevant microorganisms due to its rapid, objective, nondestructive, and cost-effective nature [6,[76][77][78][79][80][81]. Although traditional ML techniques have been widely applied for spectral data analysis [8,[98][99][100][101][102], fewer efforts have been made in developing neural networks and deep learning algorithms [103][104][105].…”
Section: Detection and Identification Of Microorganismsmentioning
confidence: 99%